2014
DOI: 10.1523/jneurosci.2734-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Global Optogenetic Activation of Inhibitory Interneurons during Epileptiform Activity

Abstract: Optogenetic techniques provide powerful tools for bidirectional control of neuronal activity and investigating alterations occurring in excitability disorders, such as epilepsy. In particular, the possibility to specifically activate by light-determined interneuron populations expressing channelrhodopsin-2 provides an unprecedented opportunity of exploring their contribution to physiological and pathological network activity. There are several subclasses of interneurons in cortical areas with different functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
4
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(97 citation statements)
references
References 28 publications
2
89
4
1
Order By: Relevance
“…Recently, Ledri et al expressed ChR2 in Gad2 interneurons that contain several subpopulations inhibitory neurons such as PV-, somatostatin (SST)-, cholecystokinin (CCK)-and neuropeptide Y (NPY)-expressing cells. They showed that optogenetically activating Gad2 interneurons inhibits principal cells and thus suppresses the epileptiform activity in hippocampus (Ledri et al, 2014). Taken together, all these experiments show that an optogenetic approach provides promise for treating epilepsy.…”
Section: Optogenetic Control Of Neurons For the Treatment Of Epilepsymentioning
confidence: 87%
“…Recently, Ledri et al expressed ChR2 in Gad2 interneurons that contain several subpopulations inhibitory neurons such as PV-, somatostatin (SST)-, cholecystokinin (CCK)-and neuropeptide Y (NPY)-expressing cells. They showed that optogenetically activating Gad2 interneurons inhibits principal cells and thus suppresses the epileptiform activity in hippocampus (Ledri et al, 2014). Taken together, all these experiments show that an optogenetic approach provides promise for treating epilepsy.…”
Section: Optogenetic Control Of Neurons For the Treatment Of Epilepsymentioning
confidence: 87%
“…However, opsin activation or inhibition of interneurons may also be effective and have started to draw attention in the past few years. Several groups have thus used channelrhodopsin-2 expressed in interneurons to control seizure activity in various in vitro and in vivo epilepsy model Ellender et al, 2014;Ledri et al, 2014;Shiri et al, 2015;Yekhlef et al, 2015). This strategy is, nevertheless, not straightforward and there are several issues that need to be addressed here.…”
Section: Identification Of the Best Opsin Strategymentioning
confidence: 99%
“…On transgenic mouse line expressing channelrhodopsin interneurons, it has been shown that blue light stimulation significantly inhibits epileptic manifestations in these models [86,87]. Despite the need to address many technological and physiological difficulties, these studies point to the possible prospects of optogenetics for the treatment of epilepsy.…”
Section: Prospects Of Optogenetics For Medicinementioning
confidence: 99%